Plane and geodetic surveying : - Johnson, Aylmer (Spon Press, 2004)
Plane and Geodetic Surveying blends theory and practice, conventional techniques and GPS, to provide the ideal book for students of surveying. Detailed guidance is given on how and when the principle surveying instruments (theodolites, Total Stations, levels and GPS) should be used. Concepts and formulae needed to convert instrument readings into useful results are explained. Rigorous explanations of the theoretical aspects of surveying are given, while at the same time a wealth of useful advice about conducting a survey in practice is provided. An accompanying least squares adjustment program is available to download from www.sponpress.com/supportmaterial. Developed from material used to teach surveying at Cambridge University, this book is essential reading for all students of surveying and for practitioners who need a 'stand-alone' text for further reading.